2015
DOI: 10.1177/1071100715575001
|View full text |Cite
|
Sign up to set email alerts
|

Double-Row Bridging Suture Fixation Augmented With Double Krackow Suture for the Repair of Avulsion of the Ossified Achilles Tendon

Abstract: Level of Evidence:Level V, expert opinion.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 17 publications
1
4
0
Order By: Relevance
“…In this study, we found that all ruptures occurred at the middle part of the calcific spur, leaving a spur base at the calcaneus. Similar radiological features have been observed in other studies [12][13][14]22]. Because the calcific spur is part of the usually painful problem of Achilles tendinopathy, we removed degenerative tissue together with the main body of the calcified spur and only preserved an approximately 5-mm-flat base at the insertional site as the stump for the bone tunnels.…”
Section: Discussionsupporting
confidence: 68%
“…In this study, we found that all ruptures occurred at the middle part of the calcific spur, leaving a spur base at the calcaneus. Similar radiological features have been observed in other studies [12][13][14]22]. Because the calcific spur is part of the usually painful problem of Achilles tendinopathy, we removed degenerative tissue together with the main body of the calcified spur and only preserved an approximately 5-mm-flat base at the insertional site as the stump for the bone tunnels.…”
Section: Discussionsupporting
confidence: 68%
“…Thus, operative management must rely on tenodesis at the tendon-bone interface. Described repair techniques for distal Achilles tendon ruptures include the use of transcalcaneal drill tunnels, 4,5 suture anchor fixation, 9,15,23,24,31 and a combination of the two. 26 The transcalcaneal tunnel technique has been largely replaced by the popularization of suture anchor fixation, which provides a less invasive option, without the increased risk of calcaneal stress fracture or need for a plantar foot incision associated with the historical transcalcaneal technique.…”
Section: Discussionmentioning
confidence: 99%
“…18 Yamaguchi et al reported a small series of 4 cases in which there was avulsion of ossified Achilles tendons from their insertion sites. 19 These injuries were repaired with double row suture anchors as well as an addition of a double Krakow suture augment. In their case series, there were no incidences of repair failure or tendon rupture postoperatively.…”
Section: Discussionmentioning
confidence: 99%